Measurement of the tensor analyzing power component T20 for the incoherent neutral-pion photoproduction on a deuteron; Physical Review C; Vol. 106, iss. 2 - Vasilishin B. I. Bogdan Ivanovich; Fiks (Fix) A. I. Alexander Ivanovich; Gauzshteyn (Gauzshtein) V. V. Vyacheslav Valerjevich; Darwish E. M. Eed; Kuzin M. Ya. Matvey Yaroslavovich (2022, 2022)
Title screen